PHF21B as a candidate tumor suppressor gene in head and neck squamous cell carcinomas - Bertonha, Fernanda Bernardi; Barros Filho, Mateus de Camargo; Kuasne, Hellen; Reis, Patricia Pintor dos [UNESP]; Prando, Erika da Costa [UNESP]; Augusto Moyano Munoz, Juan Jose; Roffe, Martin; Maroso Hajj, Glaucia Noeli; Kowalski, Luiz Paulo; Rainho, Claudia Aparecida [UNESP]; Rogatto, Silvia Regina [UNESP] (Elsevier B.V., 2015)
A significant association between DNA losses on 22q13.31 and head and neck squamous cell carcinomas (HNSCC) was previously reported by our group. Our data indicated that PHF21B gene, mapped on 22q13.31 and encoding a protein with function of chromatin-mediated transcriptional regulation, might be a putative tumor suppressor gene. To test this hypothesis, gene copy number was assessed in 75 HNSCC and 49 matched peripheral blood samples. PHF21B losses were detected in 43 tumors and were significantly associated with patients with familial history of cancer (P < 0.0001); i.e., 36/43 cases showed a positive family history of cancer and 22/36 had first-degree relatives with cancer (P = 0.049). In attempt to investigate other mechanisms for PHF21B loss of function, DNA sequencing was performed and no mutations were detected. We next evaluated the gene expression levels after inhibition of DNA methylation in nine HNSCC and breast carcinoma cell lines. Additionally, PHF21B expression levels were evaluated in colon cancer HCT116 cells as well as in its counterpart DKO (double knockout of DNMT1 and DNMT3B). The higher expression levels of PHF21B gene detected in DKO cells were inversely correlated with the DNA methylation. Further, DNA methylation in the specific promoter-associated CpG Island was investigated. Interestingly, gene hypermethylation was detected in 13/37 tumors: 5/13 HNSCC cases had family history of cancer in first-degree relatives and 8/13 showed both, DNA methylation and PHF21B losses in the tumor sample. One patient had PHF21B loss in the peripheral blood cells and PHF21B methylation in the tumor sample. Additionally, overexpression of PHF21B in cell lines drastically reduces clonogenic and migratory abilities. These data suggest that PHF21B is a novel tumor suppressor gene that can be inactivated by genetic and epigenetic mechanisms in the human cancer. (C) 2014 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: HNSCC; Tumor suppressor gene; PHF21B; Epigenetic changes; Copy number alterations